2015
DOI: 10.22605/rrh3019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of barriers to adoption of buprenorphine maintenance therapy by family physicians

Abstract: Introduction: Opioid abuse has reached epidemic levels. Evidence-based treatments such as buprenorphine maintenance therapy (BMT) remain underutilized. Offering BMT in primary care settings has the potential to reduce overall costs of care, decrease medical morbidity associated with opioid dependence, and improve treatment outcomes. However, access to BMT, especially in rural areas, remains limited. This article will present a review of barriers to adoption of BMT among family physicians in a primarily rural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 41 publications
1
82
0
Order By: Relevance
“…However, urban centers were less likely to offer specialized treatment options for adolescents. Other studies have also revealed a poorer quality of care, less access to care and more financial barriers in urban and rural treatment settings compared with suburban treatment settings (DeFlavio et al, 2015; Dew et al, 2007; Higgins et al, 2019; Hirchak & Murphy, 2017). There is a clear need to focus on removing barriers that affect the level of drug education and treatment provided within underserved rural and urban communities.…”
Section: Discussionmentioning
confidence: 99%
“…However, urban centers were less likely to offer specialized treatment options for adolescents. Other studies have also revealed a poorer quality of care, less access to care and more financial barriers in urban and rural treatment settings compared with suburban treatment settings (DeFlavio et al, 2015; Dew et al, 2007; Higgins et al, 2019; Hirchak & Murphy, 2017). There is a clear need to focus on removing barriers that affect the level of drug education and treatment provided within underserved rural and urban communities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified several “consumer-focused,” and “provider-focused” barriers to MOUD care in rural areas (Lister, Weaver, Ellis, Himle, & Ledgerwood, 2020). For instance, consumer-focused barriers (Ellis, Konrad, Thomas, & Morrissey, 2009; Kaufman et al, 2016) included the dearth of MOUD treatment options available to rural residents with OUD, while provider-focused studies (Andrilla, Coulthard& Larson, 2017; DeFlavio, Rolin, Nordstrom, & Louis A Kazal, 2015; Jones, 2018; McCarty, Gustafson, Capoccia, & Cotter, 2004) referenced barriers related to availability and acceptability of MOUD in rural communities (Lister et al, 2020). Anticipated stigma, whereby individuals come to expect particular forms of discriminatory treatment (Turan et al 2017; Van Brakel et al 2019), has also been identified as a barrier associated with MOUD—particularly agonist therapies—such that reinforcing negative attitudes may become internalized, and negatively impact on individuals’ mental health and willingness to utilize treatment (Crapanzano, Hammarlund, Ahmad, Hunsinger, & Kullar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A key systemic barrier that has been identified is the lack of access to behavioral intervention and counseling to accompany MOUD prescribing [ 16 - 18 ]. Behavioral interventions have the potential to address poor adherence to medication.…”
Section: Introductionmentioning
confidence: 99%